Peran Strategi Bisnis Terhadap Nilai Perusahaan dengan Good Corporate Governance sebagai Variabel Mediasi - Dyah Aprillya Pratiwi; Suwandi (Akuntansi : Jurnal Akuntansi Integratif, 2022)
This study aims to determine the role of good corporate governance in mediating the effect of business strategy on firm value in non-cyclical consumer companies listed on the Indonesia Stock Exchange. This research includes quantitative research. With a population of all non-cyclical consumer companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling technique, in order to obtain 26 companies as samples. Data collection techniques used documentation techniques with secondary data obtained from non-cylicals consumer companies listed on the Indonesia Stock Exchange. The data analysis technique in this study is the mediation path analysis using Smart PLS (Partial Least Square) version 3.3.9 with the PLS method consisting of Outer Model Analysis, Inner Model Analysis, and Hypothesis Testing. The results of this study prove that business strategy has no effect on firm value, business strategy has no effect on firm value with the audit committee as a mediating variable, business strategy does not affect firm value with institutional ownership as a mediating variable, business strategy does not affect firm value with the proportion independent board of commissioners as a mediating variable.